The Role of Islamic Kingdoms in the Islamization of the Nusantara: A Literature Study of Samudera Pasai, Aceh, and Mataram - Aufa Fatchia Rahma; Lutfiah Holifa Balkis; Dwi Ratnasari (Journal of Indonesian Islamic Studies, 2026)
This study aims to analyze the role of Islamic kingdoms in the Islamization process in the Nusantara through a literature study approach. The research focuses on three major Islamic kingdoms, namely Samudera Pasai, Aceh, and Mataram Islam, which played significant roles in shaping Islamic civilization in the region. This study employs a qualitative method with a literature review design, utilizing data from scholarly articles, books, and relevant academic sources. The findings reveal that Islamization in the Nusantara was a multidimensional process influenced not only by trade and ulama networks but also by political authority and cultural adaptation. Samudera Pasai functioned as an initial gateway of Islamization through trade and early institutional formation, Aceh emerged as a center of Islamic intellectual development and political consolidation, while Mataram Islam contributed through cultural integration and social adaptation. These findings indicate that the Islamization process was cumulative and complementary, involving political, educational, and socio-cultural dimensions. This study contributes to a more integrative understanding of Islamization by offering a comparative framework that connects multiple Islamic kingdoms within a unified analytical perspective.